RANCANGAN DATABASE SISTEM INFORMASI PROGRAM STUDI D3 KOMUNIKASI PENERBANGAN DI POLITEKNIK PENERBANGAN SURABAYA - Muhammad Fatkur Rozaq; Laila Rochmawati; Lady Silk Moonlight (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Abstract In today's digital era, everyone can easily use Internet access to find information. Aviation Polytechnic of Surabaya as an educational and training institution that has the main task of developing and training Surabaya Transportation Human Resources. An agency is encouraged to implement a web-based information system to make it easier to find data on the study program that is being run. The development of modern technology will increase the value of effectiveness and efficiency in an agency. Currently there is no web-based information system for the Aviation Communication Study Program at Aviation Polytechnic of Surabaya. To overcome the above, a web-based study program information system is needed that can facilitate online document data storage and provide access to study program information between the Academic Community and for the benefit of the general public. This research uses the Research and Development (R&D) research method. With the ADDIE (Analysis-Design-Develop-Implement-Evaluate) instructional design research development model. Using the WordPress as a website creation platform and the Google Drive as a study program document database. So that the creation of a web-based Aviation Communication Study Program information system can make it easier for someone to get information about the Aviation Communication Study Program.